Potensi Augmented Reality sebagai Sarana Promosi Kolaborasi dan Kerjasama Siswa dalam Pendidikan Agama di SD - Fuwa, Muhamad Nur Faizi Putra; Karisma, Linda Ayu (Jurnal Riset Madrasah Ibtidaiyah, 2024)
Religious education plays an important role in forming harmonious understanding and cooperation among students. However, challenges often arise in creating a learning environment that encourages collaboration and collaboration among students. In recent years, augmented reality (AR) technology has emerged as an innovative tool in education. This article aims to explore the potential of augmented reality in encouraging collaboration and cooperation among students in religious education. This research focuses on the use of augmented reality in the context of religious learning to create an environment that allows students to collaborate actively. By combining virtual and physical elements, augmented reality provides an immersive and interactive learning experience, and allows students to explore religious concepts in greater depth. An analysis of related studies that have been conducted in this field, serves to identify the benefits and challenges associated with using AR in creating a cooperative learning environment. In addition, discussions about strategy and pedagogy can be used to optimize the use of augmented reality in the context of religious education. By harnessing the potential of this technology, it is hoped that students will be able to have more meaningful and mutually supportive learning experiences, which in turn will strengthen their understanding of religion and promote wider intercultural cooperation.